Suitability and Eligibility of Phyllostachys pubescens (Moso Bamboo) Afforestation for GHG (Greenhouse Gases) Projects: Case Study in Central Italy - Vadalà, Rossella; Cicero, Nicola; Dugo, Giacomo; Costa, Rosaria (Frontiers in Environmental Science, 2022)
A case study concerning an experimental moso bamboo plantation (5 ha), located in central Italy, is presented. In order to evaluate CO2 capturing potential, a computational study was developed and applied to the bamboo field to predict and quantify the tons of CO2 equivalent annually sequestered, during a project range of 16 years. The computational model, based on allometric parameters and field density, was integrated with an accurate analysis of the geological, pedological and climatic scenario, and of the socio-economic context. The study aimed to correlate the growth and thickening trend of moso bamboo field, namely its CO2 capturing potential, with the geopedoclimatic context. This allowed to evaluate if the bamboo afforestation projects are capable to offset carbon dioxide emissions in the Italian context. The highest segregation power of the bamboo plantation equated 28.447 tCO2e · yr-1, segregated by the whole field in the thirteenth year (out of a total timeframe of 16 years). The study demonstrated the eligibility requirements for a GHG project and the suitability of moso bamboo farming finalized to carbon trading. Our findings represent a valid model to encourage the voluntary carbon market in Italy from afforestation with bamboo species.